Emeril's cooking with power : 100 delicious recipes starring your slow cooker, multi cooker, pressure cooker, and deep fryer /: 100 delicious recipes starring your slow cooker, multi cooker, pressure cooker, and deep fryer. ([2013]) - Lagasse, Emeril
No abstract available